Comparative evaluation of propolis mouthwash with 0.2% chlorhexidine mouthwash as an adjunct to mechanical therapy in improving the periodontitis among perimenopausal women: a randomized controlled trial - Syeda Maliha Waqar; Afifa Razi; Saima Sameer Qureshi; Fizza Saher; Syed Jaffar Abbas Zaidi; Chander Kumar (BMC, 2024)
Abstract Objective To evaluate the efficacy of Propolis mouthwash compared to chlorhexidine mouthwash as an adjunct to mechanical therapy in improving clinical parameters in perimenopausal women with chronic periodontitis. Methodology A double-blind, randomized, controlled clinical trial was conducted by recruiting 144 subjects with mild to moderate chronic periodontitis. After scaling and root planning, subjects were allocated to two treatment groups: 0.2% chlorhexidine mouthwash and 20% propolis mouthwash twice daily for six weeks. Clinical parameters such as pocket probing depth (PPD), clinical attachment loss (CAL) and bleeding on probing (BOP) were analysed at baseline, six weeks, and 12 weeks. Result The mean value of PPD in the propolis group was 4.67 at baseline, reduced to 4.01 at six weeks and 3.59 at 12 weeks. While in the chlorhexidine group, the baseline value of 4.65 reduced to 4.44 and 4.25 at six weeks and 12 weeks, respectively. The baseline value of the mean CAL in the propolis group was 4.45. This value was reduced to 4.15 at six weeks and 3.77 at 12 weeks. For the chlorhexidine group, the baseline value of CAL was 4.80, which was reduced to 4.50 and 4.19 at six weeks and 12 weeks. The mean value of bleeding on probing in the propolis group was 77.20, which decreased to 46.30 at six weeks and 14.60 at the final visit. In the chlorhexidine group, the mean value of 77.30 was reduced to 49.60 and 22.80 at subsequent visits. Conclusion This study concludes that both propolis and chlorhexidine mouthwash positively improve clinical parameters; however, propolis is significantly more effective in improving BOP. Trial registration ID: NCT05870059, Date of Registration: 02/02/2022. ( https://beta.clinicaltrials.gov/study/NCT05870059 ).